8 - Covid-19 and Knowledge Production in Africa: Entrenching Inequalities or Promising Opportunities? - Fongwa, Samuel; Kibona, Bertha; Munene, Ishmael; Mtawa, Ntimi; Wangenge-Ouma , Gerald (CODESRIA Bulletin, 2023)